2021
DOI: 10.1680/jensu.20.00064
|View full text |Cite
|
Sign up to set email alerts
|

A numerical study on the effect of vent/wall area ratio on Trombe wall thermal performance

Abstract: Trombe walls are the most widely applied passive systems that utilise solar energy for heating massive walls. Although studies have been undertaken in the fields of Trombe wall application and design, the research on the effect of the vent area and the number of vents on the performance of a Trombe wall remains limited. In this context, a parametric study investigating the effect of the vent-to-wall-area ratio on Trombe wall performance was conducted. A computational fluid dynamics model was employed for valid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…There is also a relatively complex structure compared to traditional buildings, subjected to thermal optimization studies (Demirbilek et al, 2003) by taking into consideration of glazing, thermal wall thickness, window/wall ratio and insulation material selections all at once. Phase change materials have also been used lately in improving Trombe wall efficiency by several researchers (Xiong et al, 2022;Duan et al, 2021) On the other side, CFD programs are often used by researchers when dealing with temperature distribution, air flow/circulation and ventilation problems where density changes and buoyancy effect get involved (Jaber and Ajib, 2011; Kaya et al, 2021). In this manner, vent optimization related research studies have employed and taken advantage of CFD fluent environments.…”
Section: Figure 1: Major Components and Air Circulation Mechanism Of ...mentioning
confidence: 99%
See 1 more Smart Citation
“…There is also a relatively complex structure compared to traditional buildings, subjected to thermal optimization studies (Demirbilek et al, 2003) by taking into consideration of glazing, thermal wall thickness, window/wall ratio and insulation material selections all at once. Phase change materials have also been used lately in improving Trombe wall efficiency by several researchers (Xiong et al, 2022;Duan et al, 2021) On the other side, CFD programs are often used by researchers when dealing with temperature distribution, air flow/circulation and ventilation problems where density changes and buoyancy effect get involved (Jaber and Ajib, 2011; Kaya et al, 2021). In this manner, vent optimization related research studies have employed and taken advantage of CFD fluent environments.…”
Section: Figure 1: Major Components and Air Circulation Mechanism Of ...mentioning
confidence: 99%
“…In spite of a large number of research studies undertaken, yet only few referred how to adjust vent size and dimensions for obtaining optimum performance (Briga et al, 2014;Jaber and Ajib, 2011). A recent study (Kaya et al, 2021) has pointed out this research gap and investigated the effect of total vent/wall area ratio on TWs thermal performance by increasing this ratio by 2% starting from unvented case. The results showed that any TW configuration with 8% vent/wall ratio provides maximum heating performance.…”
Section: Figure 1: Major Components and Air Circulation Mechanism Of ...mentioning
confidence: 99%